Tibouchina granulosa Purple Glory Tree - Edward Gilman (EDIS, 2024)
This document provides an overview of Tibouchina granulosa, commonly known as the purple glory tree. It describes the plant’s characteristics, including its moderate growth rate, dense foliage, and large, vibrant purple flowers that bloom throughout much of the year. The plant can be trained into a small tree or maintained as a shrub, making it versatile for various landscape uses such as screens, specimen plants, or container gardening. The document also covers the plant’s cultural requirements, including its preference for full sun and well-drained soil, as well as its propagation methods and pest resistance. Emphasis is placed on its suitability for USDA hardiness zones 10B through 11. Original publication date October, 1999.